Analisis Kurikulum Pendidikan Islam Implementasi Kurikulum Muatan Lokal Aksara Arab Melayu MIS Terpadu Muhammad Fahri - Mursal Aziz; Husna Ibrahim; Khoirul Bariah Rambe; Rahmi Wirdayani Adelia (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
This research aims to explain and describe the Islamic education curriculum implementing local content curriculum in the learning of Malay Arabic Script at Muhammad Fahri Integrated MIS. This research uses a qualitative descriptive approach, data was obtained through observation, interviews and documentation carried out at Mahammad Fahri Integrated MIS. The results of the research show that the Islamic education curriculum implementing local content curriculum in Malay Arabic script subjects is taught from grade one to grade six, this learning is carried out in schools and continued at MDTA. The learning resources used are books owned by the teacher. Learning methods include introducing hijaiyah letters, writing letters, recognizing and writing words, as well as various Malay Arabic script exercises. The challenge experienced by the teacher in this lesson was the students' difficulty in writing letters and translating from Indonesian or Latin to Malay Arabic script. Efforts made by teachers to overcome these obstacles include repeating material, providing examples, and providing various exercises to hone students' skills.